Stabilisation of expansive subgrade soils with slag and cement for road construction - Ika Putra, Agus (Curtin University, 2014)
This research evaluates stabilisation of expansive soil as a subgrade for road pavement. The recommended stabiliser proportion was 13.5% slag + 1.5% cement at 28 days curing time, which based on obtaining UCS test results that eight times magnitudes higher than the strength of the non-stabilised soil. The CBR values were more than four times higher than the minimum required for designing road pavement. The best resilient modulus correlation model was the hyperbolic correlation model.